Time-domain analysis of adaptive interference cancellation system with the desired signal - Wen-lu LI; Zhi-hua ZHAO; Yi LI; Jian TANG; Huan XIAO (Tongxin xuebao)
A time-domain model for adaptive interference cancellation system (AICS) involving both interference and desired signal was proposed.According to the theoretical analysis,the performances of AICS,such as desired signal cancellation ratio (SCR),interference cancellation ratio (ICR) and convergence time,were analyzed in detail.It was found that the AICS feedback circuit should be in the condition of low damping in order to reduce the negative effect of desired signal.The influences of several parameters on the performances of the AICS were obtained.The experimental results are in agreement with theoretical analysis,which is of great value to the optimization design of the AICS.